2021
DOI: 10.3390/brainsci11081098
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Vitamin E and the Orexin System in Neuroprotection

Abstract: Microglia are the first line of defense at the level of the central nervous system (CNS). Phenotypic change in microglia can be regulated by various factors, including the orexin system. Neuroinflammation is an inflammatory process mediated by cytokines, by the lack of interaction of specific receptors such as the OX2-OX2R complex, caused by systemic tissue damage or, more often, associated with direct damage to the CNS. Chronic activation of microglia could lead to long-term neurodegenerative diseases. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 164 publications
0
13
0
Order By: Relevance
“…One clinical study carried out to lower the effect of cisplatin chemotherapy neurotoxicity, the supplementation with vitamin E (alpha tocopherol) has shown lower level of neurotoxicity, which indicates that vitamin E plays a neuroprotective role [42] even when the cause of neurotoxicity could be other than mild cognitive impairment. The findings of Gugliandolo et al ( 2017) have reported similar physiological responses of Vitamin E on MCI [43][44][45]. Another study by Kaneai et al, indicated that vitamin E offers some neuroprotective benefits by improving neurotransmission [45].…”
Section: Discussionmentioning
confidence: 81%
“…One clinical study carried out to lower the effect of cisplatin chemotherapy neurotoxicity, the supplementation with vitamin E (alpha tocopherol) has shown lower level of neurotoxicity, which indicates that vitamin E plays a neuroprotective role [42] even when the cause of neurotoxicity could be other than mild cognitive impairment. The findings of Gugliandolo et al ( 2017) have reported similar physiological responses of Vitamin E on MCI [43][44][45]. Another study by Kaneai et al, indicated that vitamin E offers some neuroprotective benefits by improving neurotransmission [45].…”
Section: Discussionmentioning
confidence: 81%
“…For example, thyme, turmeric, coriander and beetroot juice are excellent sources of vitamin C [146]. Vitamin E is also an important antioxidant molecule, especially in relation to alpha-tocopherol, and many studies analyzing its fundamental effects have been conducted, especially on the brain and nervous system, aiming for the prevention of neurodegenerative diseases [147,148]. Tocopherols are mainly found in edible oils, such as corn, soy, sesame and rapeseed (canola) oils, or in walnuts [149].…”
Section: Anti-inflammatory and Antioxidant Foods To Prevent Cancermentioning
confidence: 99%
“…Furthermore, the effects of vitamin E (Tts reach fraction and α-Toc) in protecting astrocytes against glutamate injury acted as a potent antioxidant agent in recovering mitochondrial injury due to elevated oxidative stress [75]. The neuroprotective effects of vitamin E, especially those of tocotrienols, have also been well documented in many other in vitro and in vivo studies [31][32][33][34][35][36][37]76]. Thus, based on the available results, it seems legitimate to infer a protective effect of vitamin E expressed in the reduction of the release of LDH induced by H 2 O 2 .…”
Section: Neuroprotective Activity Of Tocochromanolsmentioning
confidence: 99%